2021
DOI: 10.1002/ppul.25570
|View full text |Cite
|
Sign up to set email alerts
|

Impact of nonpharmacological COVID‐19 interventions in hospitalizations for childhood pneumonia in Brazil

Abstract: Background and Objective: The knowledge about the impact of the nonpharmacological measures to control the COVID-19 pandemic can give insight into ways in which they can also be applied for other respiratory diseases. To assess the impact of containment measures of the COVID-19 pandemic on pneumonia hospitalizations in children from 0 to 14 years of age in Brazil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 28 publications
(73 reference statements)
0
7
0
3
Order By: Relevance
“…Other countries reported a massive decrease in pediatric CAP after NPIs implementation [23,24]. Among these countries, some experienced an important total duration of school closure (57 weeks in Brazil), whereas other decided to limit this measure (12 weeks in France and 6 weeks in Switzerland) [25].…”
Section: Discussionmentioning
confidence: 99%
“…Other countries reported a massive decrease in pediatric CAP after NPIs implementation [23,24]. Among these countries, some experienced an important total duration of school closure (57 weeks in Brazil), whereas other decided to limit this measure (12 weeks in France and 6 weeks in Switzerland) [25].…”
Section: Discussionmentioning
confidence: 99%
“…Using an interrupted time-series design approach, we showed that decreased hospitalized patients and deaths from communityacquired pneumonia coincided with rising public awareness of personal precautions before the governmental CACPs. During the COVID-19 pandemic, a decrease in non-COVID-19 pneumonia has been reported worldwide, 3,[30][31][32][33] which was often attributed to the implementation of a wide range of NPIs including universal mask mandates, physical distancing policies, and lockdowns. However, the relative contributions of different types of NPIs are not necessarily well understood; the reduction in community-acquired pneumonia during the COVID-19 pandemic that has been reported to date was observed in the context of concurrent implementations of CACPs and personal precautions by the general public, and their separate effects could not be estimated.…”
Section: Discussionmentioning
confidence: 99%
“…This data analysis methodology has been well documented in the literature. 7,9 The Brazilian National Health Agency provides the percentage of the population that has health insurance per year, which we excluded from the denominator. 17 To evaluate the effect of COVID-19-containment strategy on the incidence of asthma, the average incidence (hospitalizations per 100,000 inhabitants [Brazilian Institute of Geography and Statistics]) 14 of each month (April-December) of the 2016-2019 set was compared with the incidence of asthma in the period April to December of 2020, in each age group analyzed (1-14 years, 20-59 years, and older than 60 years).…”
Section: Statisticsmentioning
confidence: 99%
“…4 Such measures may impact the epidemiology of various respiratory diseases all around the world. 3,[5][6][7][8][9][10] Patients with chronic respiratory diseases can benefit from these measures. Chronic respiratory diseases are diseases of the airways and other structures in the lung.…”
mentioning
confidence: 99%